The Importance of the Mining Sector for the Economic Development of sub-Saharan African Countries Using Angola as an Example - Dymitrowska, Yanina (Studia Oeconomica Posnaniensia, 2017)
A significant part of Sub-Saharan African countries are specializing in the extraction and export of natural resources. In most of them the resource curse or visible symptoms of the Dutch disease occur. One Sub-Saharan African country, Botswana, managed to avoid the negative effects of the phenomenon. In the next three - Angola, Mozambique and Rwanda - positive changes in economic development have been reported in recent years. The paper presents the results of an assessment of the economic development of Angola in the context of the occurrence of the resource curse in the years 1995-2014.